Why They Fight: Ideology and Terrorist Motivation - Holbrook, Baldvin Donald (Terrorism and political violence, 2025)
There is a disconnect between the ideological and political nature of terrorism, on the one hand, and the apparent motives of terrorists on the other, where identification with that political and ideological context is often seen to be limited. This is arguably a central dilemma in the study of terrorism, which has practical implications too. In this article, I develop a three-pronged approach to address this dilemma. First, I explore how our theoretical understanding of ideology can underpin and expand our understanding of terrorist motivation and the distinctive characteristics of terrorism as political violence. Second, I explore the function of ideology empirically through direct observations of the role ideology played for convicted terrorists in the UK. Third, I draw observations from these two perspectives to address the challenges of ideological bricolage and ‘hybrid’ extremism.